A UPLC-Q-TOF-MS-Based Metabolomics Approach to Screen out Active Components in Prepared Rhubarb for Its Activity on Noxious Heat Blood Stasis Syndrome - Zhu, Hui; Duan, Yu; Qin, Kunming; Jin, Junjie; Liu, Xiao; Cai, Baochang (Frontiers in Pharmacology, 2022)
Background: Prepared rhubarb was obtained by steaming the raw rhubarb with wine. Different from the raw rhubarb with purgative effect, prepared rhubarb shows effects of promoting blood circulation and removing blood stasis. However, the mechanisms of its action way through regulating endogenous metabolites remain unclear. Purpose: The purpose of this paper was to explore active chemical components in prepared rhubarb for its activity on noxious heat blood stasis syndrome (NHBS) by comprehensive metabolomics profiling. Study design: Plant extracts usually show their activities in a synergistic way, therefore, integrated omics was developed as a rational way for better understanding of its biological effects and potential active compounds. Methods: Activities of prepared rhubarb was evaluated by biochemical and metabolomic analysis, meanwhile, serum chemical profiles were sought using UHPLC-Q-TOF-MS. Gray correlation analysis (GCA) was employed for calculating underlying correlations between them. Results: The metabolomics profiles of rat plasma from model and control groups were significantly different, with 31 endogenous metabolites changed by NHBS. Then, after administration of prepared rhubarb, 18 of them were regulated. Multiple metabolic pathways were disturbed after NHBS modeling and restored by prepared rhubarb, among which it had a greater impact on sphingolipid metabolism. A total of 28 compounds from prepared rhubarb absorbed into plasma were identified, including 9 prototypes and 19 metabolites. Statistical results suggested that rhein and its metabolites accounted for half the top 10 active compounds in prepared rhubarb for its biomedical activities. Conclusion: This study presented evidence for the therapeutic effects and active chemicals of prepared rhubarb on NHBS in way of metabolomics.